Exercise Pre Operatif pada Pasien Kanker Payudara dengan Mastektomi - Nurmalasari Nurmalasari; Allenidekania Allenidekania (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the effect of preoperative exercise on breast cancer patients with mastectomy. The research design is a systematic review using the PubMed, ScienceDirect, and Scopus databases. The research results obtained 199 articles and nine articles were relevant and met the requirements. The preoperative exercise showed a positive effect on the side effects of mastectomy. In conclusion, preoperative exercise intervention can reduce complaints or side effects felt by breast cancer patients after undergoing a mastectomy, including pain, limited range of motion of the shoulder joint, decreased shoulder function, lymphedema, and quality of life. Keywords: Preoperative Exercise, Breast Cancer, Mastectomy